Exploring the Effect of Aspect to Inform Future Earthcasts of Climate‐Driven Changes in Weathering of Shale. Issue 4 (10th April 2019) - Sullivan, P. L.; Goddéris, Y.; Shi, Y.; Gu, X.; Schott, J.; Hasenmueller, E. A.; Kaye, J.; Duffy, C.; Jin, L.; Brantley, S. L.
Abstract: Projections of future conditions within the critical zone—earthcasts—can be used to understand the potential effects of changes in climate on processes affecting landscapes. We are developing an approach to earthcast how weathering will change in the future using scenarios of climate change. As a first step here, we use the earthcasting approach to model aspect‐related effects on soil water chemistry and weathering on hillsides in a well‐studied east‐west trending watershed (Shale Hills, Pennsylvania, USA). We completed model simulations of solute chemistry in soil water with and without the effect of aspect for comparison to catchment observations. With aspect included, aqueous weathering fluxes were higher on the sunny side of the catchment. But the effect of aspect on temperature (0.8 °C warmer soil on sunny side) and recharge (100 mm/year larger on shaded side) alone did not explain the magnitude of the observed higher weathering fluxes on the sunny side. Modeled aspect‐related differences in weathering fluxes only approach field observations when we incorporated the measured differences in clay content observed in augered soils on the two hillslopes. We also had to include a biolifting module to accurately describe cation concentrations in soil water versus depth. Biolifting lowered some mineral dissolution rates while accelerating kaolinite precipitation. These short‐duration simulations also highlighted that the inherited differences in particle size on the two sides of the catchment might in themselves be explained by weathering under different microclimates caused by aspect—over longer durations than simulated with our models. Key Points: Aspect‐related differences in solar radiation in watersheds affect both the fluxes and extents of weathering from short to long timescales Reactive transport models of weathering suggest biolifting by vegetation slows mineral dissolution rates during weathering of shale Earthcasts of weathering fluxes must model not only geochemical processes but also erosion and biotic cycling rates